Echo Chamber dan Spiritualitas Dialog Katekis dalam Terang Fratelli Tutti - Yuni Setiani Merlianta Girsang; Monica Innanda Chiaralazzo; Intansakti Pius X (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of digital media has brought significant changes to social and religious life, including the practice of catechesis. One phenomenon emerging from the digital environment is the echo chamber, a condition in which individuals are predominantly exposed to information, opinions, and perspectives that align with their existing beliefs. This phenomenon can limit critical thinking, strengthen prejudices, reduce openness to different viewpoints, and hinder constructive dialogue. As a result, the digital space may become a place of polarization rather than mutual understanding.This article aims to examine the phenomenon of echo chambers in relation to the spirituality of catechetical dialogue in the light of Pope Francis’ Fratelli Tutti. Through a qualitative and theological reflection, the study highlights the relevance of dialogue spirituality as a means of fostering openness, mutual listening, respect, and fraternity amid diversity. Pope Francis emphasizes that authentic dialogue enables individuals to encounter others, appreciate differences, and seek the common good together. Therefore, digital catechesis should not merely function as a medium for transmitting religious content but also as an inclusive and transformative space for dialogue. In this way, catechesis in the digital era can help believers develop critical awareness, openness to diversity, and a stronger commitment to building a culture of encounter and solidarity.